Effects of decoupled elliptical training on interlimb coordination - Keene, Abbey Rae, author; Tracy, Brian L., advisor; Stallones, Lorann, committee member; Reiser, Raoul F., II, committee member (Colorado State University. Libraries, 2009)
During human locomotion, the spinal cord produces predictable alternating muscle activation to the lower limbs to produce functional gait. The Shifter is a novel elliptical trainer with mechanically decoupled foot pads, forcing the user to deliver precisely timed alternating foot forces to maintain cadence. A 15-20 hr training program has been developed to enhance interlimb coordination. Training consists of a demanding progression of increasingly difficult skills that require the user to move their legs independently. PURPOSE: To determine if the training produced neural adaptations that underlie more independent control of the leg muscles. It was hypothesized that progressed subjects (PS) would have enhanced interlimb coordination compared to control subjects (CS), as assessed by suppression of contralateral neural overflow. METHODS: PS (N=5) and CS (N=5) were of similar age, leg press strength, adiposity, and VO2 max (all P>0.05). The subjects exerted an isometric force with the non-dominant knee extensors at 10% of maximal voluntary contraction (MVC) force under two conditions – alone (CF) or with an oscillating task by the dominant leg (OSC). For the OSC task, subjects exerted an oscillating force with the dominant knee extensors at a frequency of 0.25Hz between 0-50% of MVC, without visual feedback. Both the CF and OSC tasks were performed with (VIS) and without (NOVIS) visual force feedback of the non-dominant target force. RESULTS: The force oscillations of the dominant knee extensors were performed at approximately the same frequency, average intensity, and peak force between PS and CS groups for both VIS and NOVIS. For the CS group, during VIS and NOVIS, respectively, the target matching (P=0.015, P=0.004) and control of fluctuations (P = 0.02, P=0.015) for the non-dominant leg was degraded for OSC compared with CF conditions. In contrast, the PS group showed no change in the ability of the non-dominant leg to stay on target (P=0.2) and control force fluctuations (P=0.07) during VIS. During NOVIS the PS group exhibited no change in target matching (P=0.47) and a slight increase in force fluctuations (P= 0.018) between CF and OSC. CONCLUSIONS: These results suggest an adaptation of the nervous system that allowed the PS subjects to reduce the effects of contralateral neural overflow. Prolonged use of the Shifter could produce enhanced interlimb control in rehabilitation, athletic, and elderly populations.
Department Head: Richard Gay Israel.